Merger Conditions of Population III Protostar Binaries - Takanobu Kirihara; Hajime Susa; Takashi Hosokawa; Tomoya Kinugawa (The Astrophysical Journal, 2023)
Massive close binary stars with extremely small separations have been observed, and they are possible progenitors of gravitational-wave sources. The evolution of massive binaries in the protostellar accretion stage is key to understanding their formation process. We, therefore, investigate how close the protostars, consisting of a high-density core and a vast low-density envelope, can approach each other but not coalesce. To investigate the coalescence conditions, we conduct smoothed particle hydrodynamics simulations following the evolution of equal-mass binaries with different initial separations. Since Population (Pop) I and III protostars have similar interior structures, we adopt a specific Pop III model with the mass and radius of 7.75 M _⊙ and 61.1 R _⊙ obtained by the stellar evolution calculations. Our results show that the binary separation decreases due to the transport of the orbital angular momentum to spin angular momentum. If the initial separation is less than about 80% of the sum of the protostellar radius, the binary coalesces in a time shorter than the tidal lock timescale. The mass loss up to the merging is ≲3%. After coalescence, the star rotates rapidly, and its interior structure is independent of the initial separation. We conclude that there must be some orbital shrinking mechanism after the protostars contract to enter the zero-age main-sequence stage.